Executives’ Appraisal of Professional Competence of Office Technology and Management Graduates in Osun State Polytechnic, Iree - S. Ezeani, Nneka; Oludele, Yemisi Lydia (International Business Education Journal, 2021)
This study is carried out to investigate professional competence among graduates of the Office Technology and Management programme as appraised by their direct supervisors. The study employs a survey design.  Thirty-six (36) executives, consisting of eight females and twenty-eight males, of Osun State Polytechnic, Iree having the targeted graduates, who are attached to them, form the population of the study.  No sampling is made as the population is of manageable size. A self-developed questionnaire is the research instrument used for data collection.  Experts in the field validate the research instrument.  The split-half method is used to test the reliability of the instrument using ten executives from another institution, which is not part of the study population. The correlation coefficient yields 0.78, which is considered reliable.  Data collection is conducted face-to-face. The analysis reveals that the graduates are appraised to be professionally competent in administrative proficiency but slightly competent in technical, manipulative and communication proficiencies. The study concludes that Office Technology and Management graduates’ professional competence does not meet the employers’ expectations. Therefore, it is recommended that educators devise better means of implementing the training curriculum to achieve better results.